Can science end war? - Dolman, Everett (Cambridge Polity, 2016)
Is this vision of future war possible, or even inevitable? In this timely new book, Everett Carl Dolman examines the relationship between science and war. Historically, science has played an important role in ending wars ? think of the part played by tanks in breaching trench warfare in the First World War, or atom bombs in hastening the Japanese surrender in the Second World War ? but to date this has only increased the danger and destructiveness of future conflicts. Could science ever create the con-ditions of a permanent peace, either by making wars impossible to win, or so horrific that no one would ever fight? Ultimately, Dolman argues that science cannot, on its own, end war without also ending what it means to be human.
Bibliography note: Includes bibliographical references and index.
Keywords: Military art and science -- Technological innovations -- Moral and ethical aspects; Science -- Moral and ethical aspects; Military resarch -- Moral and ethical aspects; War -- Moral and ethical aspects